Effect of conjugation length on the photophysical properties of naphthyl chalcones: a DFT and experimental study - Priyanka Mahesha; Nitinkumar S. Shetty; Suresh D. Kulkarni (Discover Applied Sciences, 2025)
Abstract The design of new fluorescent chalcones with excellent photophysical properties suitable for optoelectronic applications is in high demand. In view of this, a series of naphthalene-based chalcones were synthesized by condensing 2-acetyl p-methoxy naphthalene with active aldehydes in ethanolic KOH. Density functional theory (DFT) and time-dependent DFT (TD-DFT) have been used to study chalcones’ structures, electronic absorption, and emission spectra. The absorption maxima of MNC3(346 nm), the high conjugated chalcone, exhibits a notable red shift in acetonitrile. Solid-state emission is observable in the visible spectrum’s blue-green region. Due to its open-chain extended conjugation, MNC2 showed distinct dual emission bands in acetonitrile. The minimal variation observed in fluorophores’ absorption and emission maxima in different solvents suggests that their local environment is identical. These novel compounds find applicability in light-emitting devices and the development of ratiometric probes.